An opaque pun: tentative notes on Kāsyapaparivarta § 68 - Chen, Ruixuan (Indo-Iranian journal, 2018)
Various interpretations of Kāsyapaparivarta §?68 have been attempted in the Yogācāra-Vijñānavāda tradition. This passage, which consists in a simile likening a magician devoured by his own creation to a monk involved in meditation practice, appears prima facie absurd, insofar as the similarity between the tenor and the vehicle is not readily apparent. This article mainly consists of two parts: The first part examines the received interpretations of the simile and reconstructs their interrelationship from a historical perspective. The second part explores the literary dimension of the simile and argues that its ostensible absurdity is rooted in a pun which is visible only in Middle Indo-Aryan and seems to serve no purpose. Coming to terms with the opaque and pointless pun, this essay is aimed at a new interpretation of Kāsyapaparivarta §?68 and, it is hoped, a deeper understanding of the literary playfulness inherent in the making of the Kāsyapaparivarta as a so-called early Mahāyāna sūtra against the backdrop of the Sanskritization of Buddhist sūtra literature.